Enhancement of NO2 gas sensing behavior for ZnS/PPy nanostructure by loading graphene - Ali, Iftikhar M. (Iraqi Journal of Physics, 2019)
The pure ZnS and ZnS-Gr nanocomposite have been prepared successfully by a novel method using chemical co-precipitation. Also conductive polymer PPy nanotubes and ZnS-PPy nanocomposite have been synthesized successfully by chemical route. The effect of graphene on the characterization of ZnS has been investigated. X-ray diffraction (XRD) study confirmed the formation of cubic and hexagonal structure of ZnS-Gr. Dc-conductivity proves that ZnS and ZnS-Gr have semiconductor behavior. The SEM proved that formation of PPy nanotubes and the Gr nanosheet. The sensing properties of ZnS-PPy/ZnS-Gr for NO2 gas was investigated as a function of operating temperature and time under optimal condition. The sensitivity, response time and recovery time were calculated with different operating temperatures.